2016
DOI: 10.1080/03630269.2016.1242493
|View full text |Cite
|
Sign up to set email alerts
|

Can Neuroimaging Markers of Vascular Pathology Explain Cognitive Performance in Adults With Sickle Cell Anemia? A review of the Literature

Abstract: Adults with homozygous sickle cell anemia have, on average, lower cognitive function than unaffected controls. The mechanisms underlying cognitive deterioration in this population are poorly understood, but cerebral small vessel disease (CSVD) is likely to be implicated. We conducted a systematic review using the Prisma Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines of articles that included both measures of cognitive function and magnetic resonance imaging (MRI) neuroimaging mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…This test has not previously been used in patients with CSVD. It should be noted that sickle cell anaemia is currently associated with CSVD development, as well as endothelial dysfunction and the formation of WMHs [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…This test has not previously been used in patients with CSVD. It should be noted that sickle cell anaemia is currently associated with CSVD development, as well as endothelial dysfunction and the formation of WMHs [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…13 Thus, our results suggest genotype is a stronger risk factor for poorer cognitive function than age in our cohort. This is important because although cognitive function has been well characterized in children with SCD, 8,24 few studies have examined factors that influence cognitive function during adulthood 13,25 or in milder forms of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria: (1) patients with severe visual and hearing impairment, severe physical weakness, or aphasia affecting the examination or failing to cooperate; (2) patients with mental illness or disturbance of consciousness; (3) patients who had already presented cognitive dysfunction and their assessment scores exceeding 2 points or a short caregiver questionnaire totalling more than 56 points; (4) patients who have pseudocognitive impairment or dementia caused by depression, anxiety, or AD; (5) patients whose cognitive dysfunction caused by other diseases, including infection, cancer, poisoning, metabolic diseases, and congenital mental retardation; (6) patients with severe heart, liver, lung, kidney and other organ failure, and therefore the examination cannot be completed; (7) patients who have MRI scan contraindications or are unable to scan; (8) patients whose imaging examination indicates the presence of other intracranial diseases, including cerebral hemorrhage and subarachnoid hemorrhage; (9) patients or their family are not willing to participate in the experiment.…”
Section: Inclusion and Exclusion Criteria Inclusion Criteria: (1)mentioning
confidence: 99%
“…Although the voxel-based morphology (VBM) analysis method can be used not only to analyze the difference in the gray matter structure between Alzheimer's disease (AD) patients and normal individuals but also to suggest changes in white matter structure, but whether white matter atrophy exists and its degree of damage cannot pass [6]. is method is completely deterministic, suggesting that macroscopic white matter damage detected by voxel-based morphology (VBM) does not fully reflect microscopic white matter integrity changes [7]. Diffusion tensor imaging (DTI) is a more sensitive imaging method for detecting white matter microscopic tissue damage, and it has been confirmed that DTI parameters are more closely related to MRI image volume and cognition [8].…”
Section: Introductionmentioning
confidence: 99%